Lead in paint-contaminated residential soils with varying physicochemical properties from three large US cities: assessment of geochemical forms and recommendations on amendments for immobilization - Saleh, Hadeer; Sarkar, Dibyendu; Braida, Washington; Larson, Steve; Datta, Rupali (Frontiers in Environmental Science, 2023)
Lead in yard soils has been recognized as the principal source of excess lead absorption among young children. The hazard imposed by soil lead is dependent on the geochemical forms of lead in soils. Soil properties such as pH, soil organic matter, clay, and carbonate content influence the geochemical forms of lead in soil. This study was conducted to investigate the correlation between soil properties and the geochemical speciation of lead in lead paint-contaminated residential soils from three major US cities. The influence of soil properties on geochemical speciation was analyzed to identify effective immobilization amendments for each soil type. Results showed that soils collected from San Antonio were slightly alkaline, whereas those from Baltimore were slightly acidic. Soils collected from Detroit were neutral to mildly alkaline in pH. San Antonio soils had relatively high soil salinity, high clay content, moderate to high soil organic matter (SOM), and high total carbon (TC). In contrast, soils collected from Baltimore had lower salinity and clay content, low SOM, and TC. Soils from Detroit exhibited relatively high salinity, clay, SOM, and TC contents. The average total soil lead concentrations were as follows; San Antonio 4,073 mg/kg, Baltimore 2,706 mg/kg, and Detroit 850 mg/kg. Geochemical speciation studies revealed significant differences in lead distribution among the studied soils. San Antonio soils exhibited high carbonate-bound and organic matter-bound fractions, while Baltimore soils had elevated soluble + exchangeable fractions. Detroit soils showed substantial lead in organic matter-bound fractions. Correlation analysis showed that the soil properties influencing exchangeable lead, were pH, total Al, and total Ca for San Antonio soils; pH and total P for Baltimore soils; and SOM and total Al for Detroit soils. Correlation analysis showed that there is a significant negative correlation (p<0.05) between exchangeable lead and total Al (r=-0.653), and total Ca (r=-0.438,) for San Antonio soils; pH (r=-0.286) and total P (r=-0.314) for Baltimore soils; and SOM (r=-0.628) and total Al (r=-0.408) for Detroit soils. Based on these results, the best potential immobilization amendments for each of these cities were predicted.effectiveness of these amendments in reducing lead mobility and bioavailability in paintcontaminated soils.